On the synergetic interactions between termite soldiers and workers - Castiblanco Quiroga, Gladys Julieth (2016)
A common response to predation pressure in social animals has been to allocate some individuals to defence tasks. In termites, the evolution of soldier caste was the most extreme anti-predatory response, because they are highly specialized in defence, sterile and incapable of perform self-maintenance. However, many studies have shown the active role of soldiers in tasks of space exploration like foraging. Such observations are important because the high contribution of workers in defence suggest some redundancy rate of soldier caste in termite colonies. The redundancy seems occurs in Cornitermes cumulans, where the workers being more responsive to threats than soldiers. Here we hypothesized that one way to diminish the cost of soldiers is that they are capable to do more than only defence. Specifically, we anticipate that soldiers are capable to optimize the search strategy of the workers. In the walking experiment with C. cumulans we find that the mean speed of the workers increases nonlinear with the number of soldiers. This result and the pre- sence of patterns highly coherent with Lévy flight motion suggests that the soldiers strengthen the exploratory capacity of workers in C. cumulans. In doing so, soldiers are expected to provide significant contributions to the intake of resources and to decreasing mortality in the colony. Then, our results propose an intrinsic advantage of have soldiers in the colony, and this may diminish the cost of soldiers in termite colonies.